Is poverty reduction possible? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Writing from Tanzania, I Thuwein kicks us off with a warning: 'War, malaria, AIDS and hunger are part of Africa's life and they are the source of poverty, not forgetting drought and floods. Poor communications, marketing facilities and malnutrition...